Buka minda anda panduan untuk inovasi terancang dan sistematik - Sherwood, Dennis 1949- (Institut Terjemahan Negara Malaysia Berhad, 2007)
Dennis Sherwood 'unlocks your mind' by encouraging you to think differently with stimulating exercises designed to help you draw on your own experience and knowledge in an innovative way. The techniques are widely accepted in business today, but the ways he uses them are new. Also, because Sherwood demonstrates that innovation can be a deliberate and systematic process, he shows how it can now be achieved by teams working together, pooling their mental models and ideas.